2020
DOI: 10.1186/s12882-020-01819-4
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life improved for patients after starting dialysis but is impaired, initially, for their partners: a multi-centre, longitudinal study

Abstract: Background Quality of life (QOL) is important to patients with end stage renal disease and their partners. Despite the first 12 weeks being a critical time in the treatment pathway, limited research exists which examines how the transition onto dialysis impacts QOL. In this study we measured QOL in patients and their partners at pre-dialysis and over the first 12 weeks on dialysis to investigate QOL during this crucial period. Methods Patients and their partners, recruited from 10 renal units in England, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…It was deemed likely to influence wellbeing positively and hence a carefully worded question allowed participant perspectives of ‘access’ and ‘home’ to be recorded, recognising that some people identified home as their remote community whilst others may identify it as the urban setting in which they were interviewed. This research team decision was similarly supported by reported First Nations people’s experience [ 59 ].…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…It was deemed likely to influence wellbeing positively and hence a carefully worded question allowed participant perspectives of ‘access’ and ‘home’ to be recorded, recognising that some people identified home as their remote community whilst others may identify it as the urban setting in which they were interviewed. This research team decision was similarly supported by reported First Nations people’s experience [ 59 ].…”
Section: Methodsmentioning
confidence: 66%
“…The study sought to test effectiveness of a wellbeing intervention and aimed to minimise such confounding effects where possible. That there is such a change following commencement of haemodialysis is supported by reports from First Nations people in rural Australia of a journey from ‘shock’ to ‘acceptance’ and a ‘more positive attitude’ following commencement of haemodialysis [ 59 ]. This time line also accords with findings by Moore et al (2020) of initial worsening followed by improvement in Quality of Life (QoL)12 weeks after starting dialysis [ 60 ], while others have reported that QoL deteriorates as duration of dialysis increases [ 59 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, in this study, only the HRQOLs at 3 months after dialysis start were analyzed. Recently, Moore et al [ 53 ] reported that HRQOL improves during the 3 month transition period after dialysis start, especially in physical domain. Whether HRQOL at pre-dialysis or 3 months post-dialysis is more important for survival and whether HRQOL improvement can influence patient mortality are important questions.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained at baseline (pre-dialysis) in a longitudinal study [ 11 ] were used to evaluate the performance of the individual items, internal consistency, item correlations and relatedness of the domains. This study was conducted in 10 renal research units across England.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited from the renal registries of the nephrology units from November 2017 to September 2018. The inclusion and exclusion criteria have been previously reported [ 11 ]. Briefly, patients were eligible to participate if: (1) they were in the care of a nephrologist for ESRD, (2) their clinical factors indicated that they were likely to start dialysis in the next 2 months, (3) they were planning to receive a form of out-patient HD or PD for the management of ESRD, (4) they were in a spousal-type relationship with someone they considered their “partner”, and 5) they were 18 years or older.…”
Section: Methodsmentioning
confidence: 99%